Modeling of radiant heat exchange processes - T. V. Ryabova; A. B. Sulin; A. K. Rubtsov; S. S. Muraveinikov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
It is proposed to use an imitation model with a black globe thermometer to analyze the processes of the room thermal regime formation. The model is verified by the results of a physical experiment. The indicators of the radiation factor are taken into account in the dependences of the average radiation temperature difference on the deviation of the temperature of the globe thermometer. On the basis of the proposed model, numerical experiments are performed on the example of a room model with heat-emitting panels and a cooled ceiling